FEATURES OF CYTOKINE PRODUCTION IN PATIENTS WITH RECURRENT HERPETIC INFECTION - I. A. Novikovа; O. A. Romanivа (Медицинская иммунология)
Abstract. Cytokines play an important role in resistance to herpesvirus infections. Therefore, studies of cytokine profile are necessary in recurrent herpetic infection. However, functional studies of cytokine network upon remission of the disease yielded controversial results. In this paper, we provide some results concerning comprehensive evaluation of ex vivo cytokine production by whole blood leukocytes drawn from 15 patients observed during clinical remission of recurrent Herpes Simplex virus infection. We have found a decrease of IL-1β, IL-8 and IL-10 production, as well as imbalance of cytokine profile, with predominance of IFNγ and IL-8 synthesis over IL-10 production, along with increased IL-4 and IL-13 levels to IL-1β contents. Differently directed correlations between the content of activated lymphocytes (CD3+HLA-DR+ and CD3+CD4+CD25+), natural killers (СD3-СD16/56+), NKT-cells and cytokine production levels were found in the groups of patients and healthy individuals. These differences may be due to shifts in major cytokineproducing populations in herpesvirus infections.